2003
DOI: 10.1016/s0014-5793(03)00268-0
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD99 triggers the exocytic transport of ganglioside GM1 and the reorganization of actin cytoskeleton

Abstract: We studied the role of lipid rafts and actin cytoskeleton in CD99-mediated signaling to elucidate the mechanism of protein transport upon CD99 engagement. CD99 engagement in Jurkat cells elicited the exocytic transport of GM1 as well as several surface molecules closely related with CD99 functions. In addition, CD99 molecules were rapidly incorporated into lipid rafts and appeared to rearrange the actin cytoskeleton upon CD99 stimulation. Association of CD99 with actin cytoskeleton was inhibited by methyl-L L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Particularly intriguing are the similarities between CD47 and CD99. Both localize in membrane rafts, induce very rapid caspase-independent cell death apototosis, apparently mediated by a novel apoptotic pathway, and become associated with the actin cytoskeleton upon engagement (Pettersen et al, 1999;Alberti et al, 2002;Mateo et al, 2002;Yoon et al, 2003). In this study, we demonstrate that actin is a key regulator of CD99 functions, being required both for ES cell adhesion and death.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Particularly intriguing are the similarities between CD47 and CD99. Both localize in membrane rafts, induce very rapid caspase-independent cell death apototosis, apparently mediated by a novel apoptotic pathway, and become associated with the actin cytoskeleton upon engagement (Pettersen et al, 1999;Alberti et al, 2002;Mateo et al, 2002;Yoon et al, 2003). In this study, we demonstrate that actin is a key regulator of CD99 functions, being required both for ES cell adhesion and death.…”
Section: Discussionsupporting
confidence: 52%
“…It was recently demonstrated that CD99 molecules locate within lipid rafts upon stimulation and that this localization is required for CD99 effects (Alberti et al, 2002;Yoon et al, 2003). CD99 ligation appears to generally upmodulate the expression of several other cell surface molecules (Aussel et al, 1993;Hahn et al, 1997;Choi et al, 1998;Wingett et al, 1999;Bernard et al, 2000;Yoon et al, 2003), including PS, TCR, MHC class I and II molecules, LFA-1 and ICAM-1, and induce their concentration at cell-cell contact sites. Overexpression was the result of their accelerated mobilization from cytosolic compartments to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD99 engagement increases intracellular transport of TCR and MHC molecules to the cell surface in thymocytes and elicits the exocytic transport of GM1 in Jurkat cells, accompanied by the rearrangement of actin cytoskeletons (Yoon et al, 2003). Furthermore, CD99 has been linked to the migration of monocytes (Schenkel et al, 2002) and to morphological changes in T and B cells Bernard et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The crucial biologic processes involving CD99 include lymphocyte development, cell adhesion and monocyte diapedesis, and expression of TCR, MHC class I and II as well as of some adhesion molecules (i.e., ELAM-1, VCAM-1, ICAM-1) by mobilization of these molecules from the Golgi to the plasma membrane (7)(8)(9)(10)(11)(12)(13)(14). In pathology, CD99 is found on the cell surface of EWS, acute lymphoblastic leukemia, thymic tumors, some spindle cell tumors (e.g., synovial sarcoma), hemangiopericytoma, meningioma, and malignant glioma, in which it confers high invasiveness and low survival rates (13,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%